Macroeconomic determinants of Indonesia’s economic growth: integrating industrial production index, inflation, and foreign direct investment within an Islamic welfare - Ariyani, Diyah; Ummah, Ida Latifattul; Nuraini, Dian Fitria (Prodi Magister Ekonomi Syariah FEBI UIN Walisongo Semarang, 2024)
The study explores the key macroeconomic factors influencing Indonesia’s economic growth, focusing on the roles of the Industrial Production Index (IPI), inflation, exchange rates, international trade, and Foreign Direct Investment (FDI) within an Islamic welfare framework. The purpose of this research is to examine how these factors contribute not only to material prosperity but also to social and moral welfare. The methodology involves secondary data analysis from 1983 to 2022 using econometric techniques such as multiple linear regression and path analysis. The findings indicate that IPI and FDI have significant positive effects on economic growth, while international trade has a negative impact, primarily due to Indonesia’s trade deficit. Inflation, within controlled limits, stimulates growth, but exchange rate fluctuations show an insignificant effect. The implications suggest that policies integrating macroeconomic management with Islamic welfare principles, such as maqāṣid al-sharī‘ah, can foster sustainable economic and social welfare by balancing material growth with ethical considerations.